Eksistensi Hukum Adat dalam Penyelenggaraan Pemerintahan Desa di Indonesia - Muhamad Habibullah AR (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Customary law is one of the living legal systems that continues to develop within Indonesian society. Its existence is constitutionally recognized and plays an important role in the administration of village governance. Villages, as the lowest level of government, possess strong social and cultural characteristics, making customary law a significant guideline in decision-making and conflict resolution. This study aims to analyze the existence of customary law in village governance from the perspective of state administrative law. The research method employed is normative legal research using statutory and conceptual approaches. The results indicate that customary law maintains a strategic position in village governance as long as it does not conflict with higher-level laws and regulations. Within the framework of state administrative law, customary law functions as a foundation for local policies, strengthens community participation, and supports the realization of democratic and equitable village governance.